Slime-Groove Drag Reduction Characteristics and Mechanism of Marine Biomimetic Surface - Muhan Yan; Yunqing Gu; Longbiao Ma; Jianxing Tang; Chengdong He; Junjun Zhang; Jiegang Mou (Applied Bionics and Biomechanics)
With the development of science and technology, energy consumption and demand continue to increase, and energy conservation and consumption reduction have become the primary issue facing the world. Improving the energy efficiency of ships not only helps reduce fuel consumption but also reduces carbon dioxide emissions, which is an important guarantee for the green development of the ocean and the maintenance of ecological balance. Through natural selection and adaptation to the environment after evolution, the body surface of organisms generates a variety of ways to resist adhesion and resistance of Marine organisms. Through the study of fish organisms, it is found that the body surface of general fish has mucus, which can effectively reduce the friction resistance of the body surface of fish subjected to seawater. In addition, the grooves on the body surface also help to reduce the resistance between swimming organisms and fluids. Based on the principle of bionics, the drag reduction characteristics and mechanism of fish surface mucus were analyzed. The drag reduction mechanism of bionic nonsmooth surface is analyzed from the aspect of body surface structure. On the basis of the two approaches, the characteristics and mechanism of slime and groove codrag reduction on the surface of Marine organisms were discussed in depth, so as to obtain a better new drag reduction method and provide reference for subsequent related research.